STEP.De study—a multicentre cluster-randomised effectiveness trial of exercise therapy for patients with depressive symptoms in healthcare services: study protocol - Andreas Heissel; Anou Pietrek; Melanie Schwefel; Kahar Abula; Gregor Wilbertz; Stephan Heinzel; Michael Rapp (BMJ Open)
Introduction Although exercise therapy has widely been shown to be an efficacious treatment modality for depression, evidence for its effectiveness and cost efficiency is lacking. The Sport/Exercise Therapy for Depression study is a multicentre cluster-randomised effectiveness trial that aims to compare the effectiveness and cost efficiency of exercise therapy and psychotherapy as antidepressant treatment.Methods and analysis 480 patients (aged 18–65) with an International Classification of Diseases diagnosis associated with depressive symptoms are recruited. Up to 30 clusters (psychotherapists) are randomly assigned to allocate patients to either an exercise or a psychotherapy treatment as usual in a 2:1 ratio. The primary outcome (depressive symptoms) and the secondary outcomes (work and social adjustment, quality of life) will be assessed at six measurement time points (t0: baseline, t1: 8 weeks after treatment initiation, t2: 16 weeks after treatment initiation, t3/4/5: 2, 6, 12 months after treatment). Linear regression analyses will be used for the primary endpoint data analysis. For the secondary endpoints, mixed linear and logistic regression models with fixed and random factors will be added. For the cost efficiency analysis, expenditures in the 12 months before and after the intervention and the outcome difference will be compared between groups in a multilevel model. Recruitment start date was 1 July 2018 and the planned recruitment end date is 31 December 2020.Ethics and dissemination The study protocol was approved by the ethics committee of the University of Potsdam (No. 17/2018) and the Freie Universität Berlin (No. 206/2018) and registered in the ISRCTN registry. Informed written consent will be obtained from all participants. The study will be reported in accordance with the Consolidated Standards of Reporting Trials and the Recommendations for Interventional Trials statements. The results will be published in peer-reviewed academic journals and disseminated to the public.Trial registration number ISRCTN28972230.